Pd-catalyzed decarboxylation of glutamic acid and pyroglutamic acid to bio-based 2-pyrrolidone. Issue 4 (2nd March 2015) - De Schouwer, Free; Claes, Laurens; Claes, Nathalie; Bals, Sara; Degrève, Jan; De Vos, Dirk E.
Abstract : A palladium based catalytic system was developed to decarboxylate glutamic acid and pyroglutamic acid to bio-based 2-pyrrolidone in aqueous media at 250 °C and under an inert atmosphere. Abstract : In order to recycle nitrogen from nitrogen-rich waste streams, particularly protein waste, we studied the decarboxylation of pyroglutamic acid and glutamic acid in a one-pot reaction to bio-based 2-pyrrolidone. After the screening of a wide range of supported Pd and Pt catalysts, 5 wt% Pd/Al2 O3 displayed the highest yield (70%) and selectivity (81%) for the decarboxylation of pyroglutamic acid in water at 250 °C and under an inert atmosphere. Side products originate from consecutive reactions of 2-pyrrolidone; different reaction pathways are proposed to explain the presence of degradation products like propionic acid, γ-hydroxybutyric acid, γ-butyrolactone and methylamine. An extensive study of the reaction parameters was performed to check their influence on selectivity and conversion. This heterogeneous catalytic system was successfully extended to the conversion of glutamic acid.